PEMBELAJARAN TERPADU TEMA GUNUNG MELETUS BERORIENTASI PENINGKATAN HASIL BELAJAR MENURUT A NEWTAXONOMY FOR SCIENCE EDUCATION - Fanni Zulaiha; Winny Liliawati; Taufik Ramlan Ramalis (Universitas Sriwijaya, 2014)
Implementation of science teaching in a junior high school in Bandung was not held integratedly. Therefore, this research implemented an integrated learning at volcano theme that aimed to get an overview of the improvement of learning outcomes. The research used quasi experimental method with one group pretest-posttest design. The sample was one of the class VIII student numbers by 31 people. The results showed that the implementation of integrated learning at volcano theme can improve student achievement based on a new taxonomy for science education. For further research, it is recommended to provide sufficient time for students to improve their creativity.